Analysis of the Influence of Service Quality and Trust on Patient Loyalty in Diabetic Wound Care Services: A Case Study at Rumat - Fadel Muhammad Fikri (Journal of Economics and Business UBS, 2026)
Diabetic wound care represents a long-term, high-risk service that requires continuous patient engagement to prevent severe complications such as infection and amputation. RUMAT, a diabetic wound care provider in Indonesia, faces a substantial challenge: a significant mismatch between a large market potential and its market share, compounded by a 37.91% patient dropout rate before treatment completion, predominantly after the third visit. This study analyzed the influence of service quality and trust on patient satisfaction, and the subsequent effect of satisfaction on patient loyalty, to inform patient retention strategies. Primary data were collected via a five-point Likert questionnaire from 134 active or former RUMAT patients, with a minimum of two visits, in the Jabodetabek and Bandung areas, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS, evaluating both measurement and structural models through path coefficients, R², effect size, and mediation analysis. All five proposed hypotheses were supported. Service Quality strongly influenced Satisfaction (β = 0.672; f² = 0.485), while Trust had a smaller, yet significant, effect (β = 0.282; f² = 0.085). Satisfaction significantly influenced Loyalty (β = 0.435), fully mediating the effects of both Service Quality and Trust, whose direct paths to Loyalty were insignificant. The model explained 88.6% of the variance in Satisfaction and 77.5% of the variance in Loyalty, with a Goodness of Fit of 0.8114, indicating strong model fit. These findings provide an empirical basis for RUMAT to prioritize service quality improvements, enhance transparency, and implement targeted dropout-prevention strategies.